2012
DOI: 10.1186/1865-1380-5-27
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous showering of tumor emboli in a patient with advanced primary lung cancer: a case report

Abstract: Extension of primary lung tumors into the left atrium via pulmonary veins is a well-documented phenomenon. Peripheral arterial embolism and cerebral embolism originating from a primary lung neoplasm are rare events. We report a case of simultaneous acute bilateral lower limb ischemia, bilateral renal infarction, splenic infarction and cerebral infarction as a result of multiple emboli originating from primary lung malignancy invasion of the left atrium. An emergent embolectomy revealed pathologic features of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 13 publications
0
25
0
Order By: Relevance
“…Most of them are associated with primary or secondary pulmonary malignancies, which occurred during intraoperative and postoperative periods. Only 11 cases of histologically proven primary pulmonary malignancies have been reported, in which spontaneous arterial tumor embolism caused sudden onset of symptoms . Among them, tumor emboli were seen in common femoral artery in four cases; in multiple arteries further from aorta in two cases; and in coronary artery, iliac artery, posterior cerebral artery, left cerebral artery and profunda femoris artery, and visceral artery in one case each.…”
Section: Discussionmentioning
confidence: 99%
“…Most of them are associated with primary or secondary pulmonary malignancies, which occurred during intraoperative and postoperative periods. Only 11 cases of histologically proven primary pulmonary malignancies have been reported, in which spontaneous arterial tumor embolism caused sudden onset of symptoms . Among them, tumor emboli were seen in common femoral artery in four cases; in multiple arteries further from aorta in two cases; and in coronary artery, iliac artery, posterior cerebral artery, left cerebral artery and profunda femoris artery, and visceral artery in one case each.…”
Section: Discussionmentioning
confidence: 99%
“…Schreffler et al reported a case of simultaneous acute bilateral lower limb ischemia, and bilateral renal, splenic, and cerebral infarction as a result of multiple emboli originating from a primary lung malignancy invasion of the left atrium. 9 Considering the risk of systemic embolization, mitral obstruction, or sudden death as a result of tumor thrombus shedding, to ensure the complete resection of tumor thrombus, comprehensive preoperative preparation and meticulous intraoperative surgery need to be particularly emphasized. Preoperative echocardiography, CT pulmonary angiography, as well as cardiac dynamic magnetic resonance and intraoperative transesophageal echocardiography should be performed whenever possible.…”
Section: Discussionmentioning
confidence: 99%
“…If left untreated, patients may die from sudden cardiac arrest due to cardia inflow obstruction or massive tumor embolization in the major organs [5] [6], which is one of the most serious complications. Schreffler et al reported a case of simultaneous acute bilateral lower limb ischemia, and bilateral renal, splenic, and cerebral infarction as a result of multiple emboli originating from invasion of a primary lung malignancy in the left atrium [7]. Given the risk of systemic embolization, mitral obstruction, or sudden death as a result of tumor thrombus detachment, comprehensive preoperative preparation and meticulous intraoperative surgery need to be emphasized to ensure complete resection of the tumor thrombus.…”
Section: Discussionmentioning
confidence: 99%